2016
DOI: 10.15252/embj.201591459
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional coactivator Bob1 promotes the development of follicular T helper cells via Bcl6

Abstract: Follicular T helper (Tfh) cells are key regulators of the germinal center reaction and long‐term humoral immunity. Tfh cell differentiation requires the sustained expression of the transcriptional repressor Bcl6; however, its regulation in CD4+ T cells is incompletely understood. Here, we report that the transcriptional coactivator Bob1, encoded by the Pou2af1 gene, promotes Bcl6 expression and Tfh cell development. We found that Bob1 together with the octamer transcription factors Oct1/Oct2 can directly bind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 77 publications
3
60
3
Order By: Relevance
“…Considering that Bcl-6 is the lineage-defining and functionally central transcription factor of Tfh cells, surprisingly little is known about its direct regulation. Although several transcription factors have been identified to promote early Tfh cell generation, only Tcf-1 and Bob1 have been shown to directly regulate Bcl-6 by binding to its promotor (42)(43)(44). In contrast, only STAT5 and Foxo1 were demonstrated to suppress Bcl-6 by direct binding to regulatory elements (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that Bcl-6 is the lineage-defining and functionally central transcription factor of Tfh cells, surprisingly little is known about its direct regulation. Although several transcription factors have been identified to promote early Tfh cell generation, only Tcf-1 and Bob1 have been shown to directly regulate Bcl-6 by binding to its promotor (42)(43)(44). In contrast, only STAT5 and Foxo1 were demonstrated to suppress Bcl-6 by direct binding to regulatory elements (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…2E). Interestingly, although POU2AF1 (encoding OCA-B), has been mainly characterised as a B-cell specific transcription factor in blood, where it plays a role in B-cell maturation (28), it has also been recently shown in mice to regulate the maintenance of memory phenotype and function in previously activated CD4 + T cells (29), and the differentiation of T follicular helper (Tfh) cells in the tissue (30). In agreement with this putative tissue-resident phenotype, pseudotime analysis demonstrated that these cells correspond to a highly differentiated cell state (Fig.…”
Section: Multi-omics Immunophenotyping Approach Identifies Rare Populmentioning
confidence: 99%
“…Transcription factor activity according to SCENIC analysis tracked the trend from Th1-like at day 9 (Runx2, Runx3, Prdm1) to TFH-like at day 30 (Lef1, Pou2af1) ( Fig. 4g) 32,33 . In addition, a consistent subset of genes associated with lung residency (Tnfrsf4, Vps37b, Fth1, Crem) was detected by differential expression analysis between lung and LN at each separate time point ( Supplementary Fig.…”
mentioning
confidence: 93%